Voluntary turnover: What we measure and what it (really) means - Matthias Georg Will (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2017)
In this paper, we run regression analyses to explain voluntary turnover intentions with data from more than 5,000 employees and with about 250 explanatory variables. The findings of our multi-factor approach highlight the fact that previous empirical research might have over-estimated the impact and significance of many factors. We show the relevance of the so-called omitted variable bias to our findings and present an empirical approach to gain estimations that are more accurate. Our approach can estimate in detail the relevance of different factors from the following categories: (a) employees' satisfaction, (b) industry, (c) firm size, (d) status and position, (e) commuting and working hours, (f) income, incentives and fairness, (g) career development, (h) health, (j) political orientation, (k) demographics, and (l) personality traits. – – Dieser Beitrag präsentiert mehrere Regressionsanalysen zur Erklärung freiwilliger Fluktuation. Die Schätzungen bauen auf einem Datensatz mit über 5.000 Personen und ca. 250 erklärenden Variablen auf. Die Ergebnisse deuten darauf hin, dass bisherige empirische Beiträge den Einfluss und die Signifikanz vieler Faktoren überschätzt haben. Aufgrund der Vielzahl an erklärenden Variablen hebt dieser Aufsatz die Bedeutung des so genannten ,,omitted variable bis“ für die empirische Fluktuations-Forschung hervor. Vor dem Hintergrund des umfangreichen Datensatzes untersucht dieser Beitrag detailliert die Effekte (a) der Arbeitnehmerzufriedenheit, (b) Branche, (c) Unternehmensgröße, (d) von Status und Position, (e) des Pendelns und der Arbeitszeit, (f) von Einkommen, Anreizen und Fairness, (g) der Karriereentwicklung, (h) Gesundheit, (j) politischen Orientierung, (k) verschiedener demographischer Variablen und (l) unterschiedlicher Persönlichkeitsmerkmale auf die Wahrscheinlichkeit, freiwillig den Arbeitsplatz zu wechseln.
urn:nbn:de:gbv:3:2-67749
Keywords: J28; J63; C13; 330; Voluntary Turnover; SOEP; Regression; Econometrics; Fluktuation; SOEP; Regressionsanalyse; Ökonometrie